Human alveolar macrophages: comparison of phagocytic ability, glucose utilization, and ultrastructure in smokers and nonsmokers - Harris, James O. (1970)
Phagocytic ability, glucose utilization, and ultrastructural morphology were studied in human alveolar macrophages in smokers and nonsmokers. The macrophages were obtained by bronchopulmonary lavage and the studies were carried out in vitro in the absence of smoke. Phagocytic ability was measured as the decrease in the number of viable Staphylococcus albus organisms incubated with the macrophages. Measurements of (14)CO(2) formation from glucose-U-(14)C were made in a resting state. 90-95% of the cells obtained by lavage were large mononuclear macrophages of which approximately 90% remained viable at the end of the experiment. Smokers yielded many more macrophages per lavage (mean 46.4 × 10(6) ±7.4) compared to the nonsmokers (mean 10.2 × 10(6) ±2.3). The decline in viable organisms was the same in each group, indicating phagocytic competence of alveolar macrophages removed from smokers. However, the mean glucose utilization for the smokers was 4.3 ±0.2 mμmoles/10(6) cells and 1.4 ±0.7 mμmoles/10(6) cells for the nonsmokers. This very significant difference (P < 0.0001) suggests that smokers' macrophages have a higher resting energy requirement than those of nonsmokers. Comparison of the ultrastructural morphology of the alveolar macrophages from each group reveals that the cells from smokers differ from those of nonsmokers in that they are slightly larger, and contain more golgi vesicles, endoplasmic reticulum, and residual bodies. The residual bodies in smokers' cells contain distinctive fiber-like inclusions.